The effect of membrane softeners on rigidity of lipid vesicle bilayers: Derivation from vesicle size changes. (January 2018) - Elsayed, Mustafa M.A.; Ibrahim, Marwa M.; Cevc, Gregor
Graphical abstract: Highlights: A simple method for quantifying the effect of bilayer softeners on deformability of bilayer vesicles is proposed. The bending rigidity of vesicle bilayers is derived from vesicle size changes caused by association of a bilayer softener. The method is used to study the effects of three bilayer softeners on deformability of phosphatidylcholine bilayer vesicles. The method lends itself as a tool aiding optimization of deformable vesicles as carriers for drug delivery across the skin. Abstract: Deformability is not just a fundamentally interesting vesicle characteristic; it is also the key determinant of vesicle ability to cross the skin barrier; i.e. skin penetrability. Development of bilayer vesicles for drug and vaccine delivery across the skin should hence involve optimization of this property, which is controllable by the concentration of bilayer softeners in or near the vesicle bilayers. To this end, we propose a simple method for quantifying the effect of bilayer softeners on deformability of bilayer vesicles. The method derives the bending rigidity of vesicle bilayers from vesicle size dependence on softener concentration. To exemplify the method, we studied mixtures of soybean phosphatidylcholine with anionic sodium deoxycholate, non-ionic polyoxyethylene (20) sorbitan oleyl ester (polysorbate 80), or non-ionic polyoxyethylene (20) oleyl ether (C18:1 EO20, Brij ® 98). With each of the tested bilayer softeners, the bending rigidity of the resulting mixed-amphipat vesicle bilayers decreased quasi-exponentially as the concentration of the bilayer softener increased, as one would expect on theoretical ground. The bilayer bending rigidity reached low values, near the thermal stability limit, i.e. k B T, before vesicle transformation into non-vesicular aggregates began. For a soybean phosphatidylcholine concentration of 5.0 mmol kg −1, the bilayer bending rigidity reached 1.5  k B T at the total deoxycholate concentration of 4.1 mmol kg −1 and 3.4  k B T at the total polysorbate 80 concentration of 2.0 mmol kg −1 . In the case of C18:1 EO20, the bilayer bending rigidity reached 1.5  k B T at the bilayer surface occupancy α  = 0.1. The dependence of vesicle size on bilayer softener concentration thus reveals vesicle transformation into different aggregate structures (such as mixed micelles with poor skin penetrability) and practically valuable information on vesicle deformability. Our results compare favorably with results of literature measurements. We provide practical guidance on using the new analytical method to optimize deformable vesicle formulations.